(untitled) (Journal of Ideas in Health, 2023)
Background: Leptospirosis is an important disease of global distribution affecting humans and animals in the tropical and subtropical regions caused by pathogenic Leptospira serovars. It’s an occupational disease with little information in Unguja Island, Zanzibar. Methods: A cross-sectional study was conducted in four selected slaughter facilities to determine the seroprevalence for Leptospira infection in slaughtered cattle in Unguja Island, Zanzibar. The blood samples and demographic data from 355 slaughtered cattle were collected and sera were separated for the Microscopic Agglutination Test (MAT) by using five types of Leptospira serovars; Hebdomadis, Sokoine, Lora, Grippotyphosa and Pomona with cutoff titer ≥ 1:40. The Chi-square test at p < 0.05 was used to assess the association between the variables and seropositivity of Leptospira infection. Results: The overall seroprevalence of Leptospira infection in the slaughtered cattle sampled was 13.0% (46/355). The predominant serovars from the tested serogroups were Hebdomadis (3.9%), followed by Pomona (2.8%), Grippotyphosa (2.8%), and Lora (2.3%); while the least reacted was Sokoine (1.1%). The body condition score was the only significant significant variable (χ2=103.9038, p=0.00001) associated with Leptospira infection seropositivity. Conclusion: The study offers the first report on the Leptospira seroprevalence in slaughtered cattle on Unguja Island. This might be a probable source of infection to slaughter facilities workers and other animals encroaching on the area. Therefore, precautions should be observed to prevent infection, especially for slaughter facility workers in Unguja.